Effect of ultrasonic treatment on structure and antitumor activity of mycelial polysaccharides from Cordyceps gunnii - Zhu, Zhen-Yuan; Pang, Wei; Li, Yuan-Yuan; Ge, Xiao-Ran; Chen, Li-Jing; Liu, Xiao-Cui; Lv, Qiang; Dong, Guo-Ling; Liu, An-Jun; Zhang, Yongmin (Carbohydrate polymers, 2014)
•Cordyceps gunnii is also well known as the Chinese rare caterpillar fungus.•The polysaccharide (MPCG-1) was isolated from the mycelium of Cordyceps gunnii.•The optimum ultrasonic processing conditions to obtain MPCG-2 were determined.•The chemical structure of MPCG-1 and MPCG-2 was investigated and compared.•Ultrasonic treatment is an effective way for enhancing antitumor of polysaceharide. Taking mycelial polysaccharides from Cordyceps gunnii (C. gunnii) as the study subject, the effect of ultrasonic power, time and concentration of polysaccharides on antitumor activity of the polysaccharides was investigated. The ultrasonic processing condition of the polysaccharides was optimized by using orthogonal test design, and determined to be 400W, 15min and 1g/L. The change of structures of polysaccharides before and after ultrasonic treatment was also studied. Results show that ultrasonic treatment did not change the characteristic attribute of polysaccharides from C. gunnii. The composition of monosaccharide residues and the category of glycosidic bond have not been changed. But the molecular weight and intrinsic viscosity was reduced, and the alpha-helicity was enhanced after ultrasonic treatment. It was possible that ultrasonic treatment is an effective way for enhancing antitumor activity of polysaccharides.